Study of cross protection of citrus tristeza viruse disease on Bendizao mandarin (Citrus succosa) - CUI Bo-fa; CUI Sheng-wei; WANG Hong-xiang; WENG Fa-ling; GONG Ji-qiang (浙江大学学报. 农业与生命科学版)
The disease samples were collected from over 20-year old trees of Bendizao mandarin (Citrus succosa) in Huangyan, Zhejiang Province, China during 1995-1996. Eighteen CTV (Citrus tristeza virus) isolates were identified on the indicator plant Mexican lime (Citrus aurantifolia). Based on the stem pit number per sq.cm on the plant, the virulence of those isolates was graded as mild (7 isolates), intermediate (5 isolates) and severe (6 isolates). In the greenhouse test, the treatment with Mexican lime plants inoculated by mild or intermediate isolates first and then challenged by severe one showed significantly reduced stem pit number per sq. cm in comparison with ones inoculated with severe isolate alone. The growth of the treatment was better than ones inoculated with severe isolate alone. It was showed the plants inoculated by mild or intermediates isolates were significantly cross protection against infections of the severe isolate. In the field experiment, Bendizao seedlings with Poncirus trifoliata or Citrus aurantium as stock were inoculated by CTV isolates with different levels of virulence respectively, and then transplanted in field. The field survey was conducted during the 5th-7th years after transplanting. The 3-yr average of small fruits percentage of the Bendizao trees pre-inoculated by mild or intermediate isolates and the trees pre-inoculated by mild and challenged by severe one was significantly lower than that of the trees inoculated by severe isolate alone and that of the uninoculated trees. It was indicated that the pre-inoculation of mild or intermediate CTV isolates showed significantly cross protection against infection of the severe ones and the natural infection in the fields. Moreover, the diseased trees infected by mild, intermediate or severe isolates, respectively, were selected at three for each from Bendizao mandarin plantation. Their yield and growth parameters were monitored for successive 3 years. The diseased trees infected by mild or intermediate isolates showed higher yield and lower percentage of small fruits than the trees infected by severe ones, indicating presence of CTV cross protection in nature.